Hybrid bio-photo-electro-chemical cells for solar water splitting - Roy I. Pinhassi (Nature Portfolio, 2016)
Photoelectrochemical water splitting uses solar power to decompose water to hydrogen and oxygen. Here, the authors integrate thylakoid membranes extracted from spinach into a bio-photo-electro-chemical cell capable of overall water splitting without the need for any sacrificial reagents.